ANALISIS PERBANDINGAN STRUKTUR KOMPOSIT PELAT BETON BALOK BAJA SEBELUM DAN SESUDAH KASTELA - Theopuspitasari, Theresia Lu; Afriadi, Yoyong (JMTS: Jurnal Mitra Teknik Sipil, 2026)
The classic problem raised in this paper is the limited capability of the original IWF steel beam concrete slab composite structure compared to the castellated IWF steel beam assembled from the original profile. The self-weight of the castellated IWF steel beam is relatively the same. The purpose of this paper is to evaluate the effect of the castellated IWF steel beam concrete slab composite structure with the original. The benefit of this paper is as information on the advantages of the castellated IWF steel beam composite structure. The structural material specifications are: the original IWF steel beam 400×200×7×11 and the castellated IWF 600×199×7×11 with openings in the hexagonal shape with the allowable base strength fs,ijin = 160 MPa, a light steel deck with ribs 7.5 cm high, a concrete slab thickness of 14 cm, and a concrete compressive strength f’c = 25 MPa. The composite beam is a simple beam with a span of 7 m. The useful width distance between the beams is 3.0 m. The composite beam elements are evaluated with Nominal Strength (ASD and Moment Strength) AISC 360-22. The study findings of the castellated IWF steel beam stress are smaller than the required allowable value, the structure is safe, the original IWF composite cross section is unsafe. The addition of moment strength is 132.41%. The short-term deflection of the original IWF composite steel beam does not meet the requirements, the long-term deflection of the castellated IWF composite steel beam is smaller than the original cross section deflection. The short-term and long-term deflection of the castellated IWF composite steel beam meets the requirements. Abstrak Permasalahan klasik yang diangkat paper ini adalah keterbatasan kemampuan struktur komposit pelat beton balok baja profil IWF asli dibandingkan balok baja IWF kastela yang dirakit dari profil aslinya. Berat sendiri balok baja IWF kastela relatif sama. Tujuan paper ini untuk mengevaluasi efek struktur komposit pelat beton balok baja IWF kastela dengan aslinya. Manfaat paper ini sebagai informasi keunggulan struktur tampang komposit balok baja IWF kastela. Spesifikasi material struktur berupa: balok baja IWF asli 400×200×7×11 dan IWF kastela 600×199×7×11 dengan bukaan pada bentuk hexagonal dengan kuatan dasar ijin fs,ijin =160 MPa, dek baja ringan dengan rusuk tingginya 7,5 cm, tebal pelat beton 14 cm, kuat desak beton f’c = 25 MPa. Balok komposit berupa simple beam bentang 7 m.  Jarak lebar manfaat antara balok 3,0 m. Elemen balok komposit dievaluasi dengan Nominal Strength (ASD dan Moment Strength) AISC 360-22. Temuan studi tegangan balok baja IWF kastela lebih kecil dari nilai izin yang disyaratkan, struktur aman, tampang komposit IWF asli tidak aman. Penambahan kekuatan momen (moment strength) sebesar 132,41%. Defleksi jangka pendek balok baja komposit IWF asli tidak memenuhi persyaratan, defleksi jangka panjang balok baja komposit IWF kastela lebih kecil daripada defleksi tampang aslinya. Defleksi jangka pendek dan jangka panjang pada balok baja komposit IWF kastela memenuhi persyaratan.